Factors distinguishing high-performing students from low-performing students in math using PISA 2018 in the Philippines - Frias, Hannah O. (Animo Repository, 2022)
In 2018, the Philippines ranked second to the last in math proficiency among the 79 other countries who participated in PISA, with 80.3% of the Filipino students not meeting the minimum standard of the assessment. With this, it is important to distinguish the high-performing students from the low-performing students and explore the factors that are significant in affecting both sets of students to shed light on variables that are of concern in terms of the student's ability to perform in mathematics. By using the Oaxaca-Blinder Decomposition model, a model that explains the difference between two groups, in terms of a dependent variable, the study examines the factors distinguishing the high-performing students from the low-performing students in terms of their math proficiency in PISA 2018.